星状神经节阻滞对前循环动脉瘤性蛛网膜下腔出血后行开颅手术患者早期脑灌注的影响(Effect of Stellate Ganglion Block on Early Cerebral Perfusion in Patients Undergoing Craniotomy for Anterior Circulation Aneurysmal Subarachnoid Hemorrhage) - 吴侑煊，王博，侯璇，梁发，韩如泉(WU Youxuan, WANG Bo, HOU Xuan, LIANG Fa, HAN Ruquan) (Zhongguo cuzhong zazhi, 2025)
目的 探讨星状神经节阻滞（stellate ganglion block，SGB）对前循环动脉瘤性蛛网膜下腔出血（aneurysmal subarachnoid hemorrhage，aSAH）后行开颅手术患者早期脑灌注的影响。 方法 本研究是早期SGB对aSAH后脑血管痉挛的影响（effect of early stellate ganglion block in cerebral vasospasm after aneurysmal subarachnoid hemorrhage，BLOCK-CVS）研究的事后分析，分析了首都医科大学附属北京天坛医院2021年7月—2023年5月纳入的进行外科手术治疗并于术前接受早期SGB治疗的前循环aSAH患者的临床资料。研究检测了aSAH患者在接受SGB前、SGB后15 min、SGB后30 min、手术结束即刻阻滞侧和对照侧的局部脑氧饱和度（regional brain oxygen saturation，rSO2），以及SGB前、SGB后30 min、手术结束即刻阻滞侧和对照侧大脑中动脉的脑血流速度（cerebral blood flow velocity，CBFV），观察SGB对脑灌注的瞬时影响。记录了术后1～3 d大脑中动脉CBFV及SGB前、SGB后3～5 d CTP参数（达峰时间、平均通过时间）的变化情况，观察SGB对脑灌注的长时改善效果。记录患者住院期间脑血管痉挛和出院后3个月复查诊断为迟发性脑缺血的发生率，评估SGB改善预后的潜在作用。 结果 研究共纳入早期接受SGB治疗的aSAH患者20例。SGB后15 min，阻滞侧rSO2较同侧基线水平显著改善[（72±6）% vs.（65±5）%，P=0.001]，rSO2随着时间的推移逐渐增加；相较于同侧基线水平，手术结束即刻rSO2最高[（78±8）% vs.（65±5）%，P＜0.001]。然而，对照侧rSO2较基线水平变化不明显。SGB后30 min，阻滞侧CBFV较基线水平降低[（107±27）cm/s vs.（117±33）cm/s，P=0.265]，对照侧CBFV无明显变化[（108±37）cm/s vs.（107±34）cm/s，P=0.968]。术后，对照侧CBFV增长速度快于阻滞侧。手术结束即刻，对照侧CBFV与同侧基线水平的差异即具有统计学意义（P=0.004），而阻滞侧在术后第3天才与基线水平的差异具有统计学意义（P=0.003）。CTP检查发现7例接受SGB患者术前合并脑局部区域灌注异常（达峰时间、平均通过时间延长），SGB后3～5 d复查显示相应脑区域灌注异常的情况均得到缓解或减轻。患者住院期间症状性脑血管痉挛和出院后3个月复查诊断为迟发性脑缺血的发生率分别为20.0%和21.1%。2例患者在SGB后5 min出现单侧喉返神经阻滞，未发现其他与SGB相关的不良事件。 结论 早期对前循环aSAH患者实施SGB可改善阻滞侧rSO2，降低同侧CBFV，改善脑灌注。Abstract: Objective To explore the effect of stellate ganglion block (SGB) on early cerebral perfusion in patients undergoing craniotomy for anterior circulation aneurysmal subarachnoid hemorrhage (aSAH). Methods This study is a post-hoc analysis of the effect of early stellate ganglion block in cerebral vasospasm after aneurysmal subarachnoid hemorrhage (BLOCK-CVS) study. It analyzed the clinical data of patients with anterior circulation aSAH who underwent surgical treatment and received early SGB before surgery, admitted to Beijing Tiantan Hospital, Capital Medical University from July 2021 to May 2023. The study measured the regional brain oxygen saturation (rSO2) on the blocked side and the control side in patients with aSAH before SGB, 15 minutes after SGB, 30 minutes after SGB, and immediately after surgery. It also measured the cerebral blood flow velocity (CBFV) in the middle cerebral artery on the blocked side and the control side before SGB, 30 minutes after SGB, and immediately after surgery, aiming to observe the transient effects of SGB on cerebral perfusion. The changes in CBFV of the middle cerebral artery within 1 to 3 days after surgery and CTP parameters (time to peak and mean transit time) before SGB and 3 to 5 days after SGB were recorded to observe the long-term improvement effects of SGB on cerebral perfusion. The incidence of cerebral vasospasm during hospitalization and delayed cerebral ischemia diagnosed at the 3-month follow-up after discharge was recorded to assess the potential effects of SGB in improving prognosis. Results A total of 20 patients with aSAH who received early SGB treatment were included in the study. Fifteen minutes after SGB, rSO2 on the blocked side significantly improved compared to the baseline level on the same side [(72±6)% vs. (65±5)%, P＝0.001] and gradually increased over time. The highest rSO2 level occurred immediately after surgery [(78±8)% vs. (65±5)%, P<0.001], compared to the baseline level on the same side. However, the changes in rSO2 on the control side compared to the baseline level were not significant. The CBFV on the blocked side decreased compared to the baseline level 30 minutes after SGB [(107±27) cm/s vs. (117±33) cm/s, P=0.265], and there were no significant changes in the CBFV on the control side [(108±37) cm/s vs. (107±34) cm/s, P=0.968]. After surgery, the CBFV on the control side increased faster than that on the blocked side. The CBFV on the control side showed a statistically significant difference from the baseline level immediately after surgery (P=0.004), while the blocked side showed a statistically significant difference from the baseline level on the 3rd day after surgery (P=0.003). CTP examination revealed that 7 patients had regional cerebral perfusion abnormalities (prolonged time to peak and mean transit time) before SGB, and the corresponding cerebral perfusion abnormalities were alleviated or relieved 3 to 5 days after SGB. The incidence rates of symptomatic cerebral vasospasm during hospitalization and delayed cerebral ischemia diagnosed at 3 months after discharge were 20.0% and 21.1%, respectively. Two patients experienced unilateral recurrent laryngeal nerve block 5 minutes after SGB, with no other adverse events related to SGB observed. Conclusions Early application of SGB in patients with anterior circulation aSAH can improve rSO2 on the blocked side, reduce the CBFV on the same side and improve cerebral perfusion.